Welfare Expenditures and the Decline of Unions - Moore, William J.; Newman, Robert J.; Scott, Loren C. (The Review of Economics and Statistics, 1989)
To what extent has the increased supply by government of certain union-like services reduced the demand for union membership and thereby contributed to the decline in trade union density? The existing empirical evidence is meager and conflicting. The puropse of our paper is to reexamine the government substitution hypothesis, specifically with respect to the relationship between government welfare spending and union density. We test the hypothesis with time-series data using three alternative models of union growth. The advantage of this approach is that it will permit an assessment of how sensitive the results are to both specification and sample period changes. In all, we find the time-series evidence of a negative welfare effect on union density to be mixed. Copyright 1989 by MIT Press.